Development of Plasma-Mig Hybrid Welding Process for Butt Joint Welding of Thick Plate Steel - Tran, Lam; Nguyen, Van Anh; Tashiro, Shinichi; Tanaka, Manabu; Nguyen, Thuc Ha (Old Journal, 2017)
Welding is present in all industrial sectors as a necessary technological process. One of the principal directions for the progress of the welding is the development of hybrid welding processes. Plasma-MIG hybrid welding was developed several decades ago. Nowadays, it becomes a bright technology in materials processing. One of the versions of the Plasma-MIG processes is basically a combination of a keyhole plasma arc with a MIG arc in order to deliver greater welding speeds, deeper weld penetration, and reduced heat input. In this paper, plate to plate butt joint welds were conducted on mild steel plates and the aims of this research is developed a Plasma-MIG hybrid welding process for single pass welding of thick steel plates. As a result, it was found that the successful single-sided welding in one pass with complete penetration and improve the weldability of welding joints in comparison with MIG welding process.